Attachment and its relevance to the ANC's attainment of hegemony by 1999 - Wolmarans, Frederik Gerhardus (University of Pretoria, 2023)
Dissertation (MSocSci (Philosophy, Politics and Economics))--University of Pretoria, 2022.